The Evolution of Very Early Onset Inflammatory Bowel Disease, Autoimmune Hepatitis, and Primary Sclerosing Cholangitis in a Young Girl - Aditi Dey (Karger Publishers, 2021)
Very early onset inflammatory bowel disease, autoimmune hepatitis (AIH), or primary sclerosing cholangitis (PSC) alone is a rare condition in young children. The combination of all 3 autoimmune disorders in a 16-month-old child is even rarer. The onset and etiology of these diseases is multifactorial and typically unknown. However, when the children are diagnosed, the accepted view point is that the inflammation was likely present for months to years prior. This case is unique because the gastrointestinal problems started from infancy, and evolved to the development of Crohn’s disease, AIH, and PSC at a very early age. This case helps bring to light that very early onset autoimmune disorders may in fact present with symptoms of feeding difficulties, growth failure, and formula intolerance. Patients may be diagnosed initially with allergic enterocolitis in infancy. Although few children with these symptoms evolve to develop autoimmune diseases at an older age, clinicians should consider following these children more closely. This case also demonstrates how hard it is to diagnose very early onset autoimmune disorders, as they mimic other illnesses.